Vitamin D deficiency is associated with metabolic syndrome in postmenopausal women. (January 2018) - Schmitt, Eneida Boteon; Nahas-Neto, Jorge; Bueloni-Dias, Flavia; Poloni, Priscila Ferreira; Orsatti, Claudio Lera; Petri Nahas, Eliana Aguiar
Highlights: Vitamin D deficiency and the increase in the prevalence of obesity are considered important public health issues. However, data for postmenopausal women are sparse and contradictory. We aimed to evaluate the association between vitamin D deficiency and metabolic syndrome in postmenopausal women. Vitamin D deficiency in postmenopausal women was associated with a higher prevalence of metabolic syndrome. Abstract: Objective: To evaluate the association between vitamin D (VD) deficiency and risk factors for metabolic syndrome (MetS) in postmenopausal women. Study design: Observational, cross-sectional cohort study. Main outcome measures: In this study, 463 women, aged 45–75 years, with amenorrhea >12 months, without VD supplementation or established cardiovascular disease were included. Clinical and anthropometric data were collected. Biochemical parameters, including total cholesterol (TC), HDL, LDL, triglycerides, glucose, insulin and 25-hydroxyvitamin-D [25(OH)D] were measured. Women meeting three or more of the following criteria were diagnosed with MetS: waist circumference >88 cm, triglycerides ≥150 mg/dL, HDL <50 mg/dL, blood pressure ≥130/85 mmHg and glucose ≥100 mg/dL. Serum 25(OH)D levels were classified as sufficient (≥30 ng/mL), insufficient (20–29 ng/mL) or deficient (<20 ng/mL). ANOVA, chi-square test and logistic regression (odds ratio, OR) were used for statistical analysis. Results: Serum 25(OH)D levels were sufficient in 148 women (32.0%), insufficient in 151 (32.6%) and deficient in 164 (35.4%). Women with low 25(OH)D levels had higher TC, triglycerides, insulin and HOMA-IR levels (p < 0.05). MetS was detected in 57.8% (182/315) of women with hypovitaminosis D (insufficient and deficient) and in 39.8% (59/148) of those with sufficient VD​​ (p = 0.003). In a multivariate logistic regression analysis, a low 25(OH)D level (<30 ng/mL) was significantly associated with MetS (OR1.90, 95%CI = 1.26–2.85), high triglyceride levels (OR1.55, 95%CI = 1.13–2.35), and low HDL levels (OR1.60, 95%CI = 1.19–2.40) (p < 0.05) compared with women with sufficient 25(OH)D levels, after adjusting for age, time since menopause, body mass index, smoking and physical exercise. The mean concentration of 25(OH)D decreased with increasing numbers of MetS components (p = 0.016). Conclusions: VD deficiency in postmenopausal women was associated with a higher prevalence of MetS. Women with VD deficiency had a higher risk of MetS, hypertriglyceridemia and low HDL than those with adequate levels.